Combination of NDT techniques in assessing external repairs of concrete - Lee, Stephen Albert O.; Antonio, Oscar Victor M. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Concrete repairs on deteriorated structures are done to improve the quality, strength and structural integrity of the building. The improvement of structural integrity as a result of these repairs can be assessed through non-destructive testing (NDT). The NDT methods used in this study were Ultrasonic Pulse Velocity and Rebound Hammer, while using the rebar scanner to know the location of the reinforcing bars. A control concrete slab and a damaged concrete structure were tested before and after repairs. In assessing the changes made, the NDT parameters were compared for damaged and repaired concrete. The obtained rebound numbers were correlated to the concrete compressive strength. The objective of this study is to create a comparison between concrete with defects and its repaired state. This will be shown by obtaining the percent difference in the pulse velocities. The minimum and maximum ultrasonic wave amplitudes as well as the frequency content were also analyzed. Data obtained from the concrete sample and at the damaged site showed that the pulse velocity increased after repairing with epoxy and mortar grout. Moreover, the maximum and minimum wave amplitudes, dominant frequency and compressive strength also increased significantly. Thus, indicating that the quality and structural integrity of the concrete test samples indeed improved.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Concrete -- Nondestructive testing